Corporate Pension Insurance as the Element of Human Resource Management - L. V. Anikeeva (Управление)
The article describes the role and position of corporate pension insurance in staff management. The obligatory pension insurance and voluntary pension insurance are examined in this article. We draw attention to reasons and conditions of corporate pension formation. There is the relation of pension rate and level of payment and way to ensure the percentage of reimbursement of pre-retirement income in the amount of pensions no lower than the level recommended by the minimum monthly wage. We point out the importance of pension insurance corporate systems in employees labor efficiency increase. How it helps to hire qualified personnel and decrease of routine business and increase of company’s competitive ability and pensioner income level growth.